2016
DOI: 10.4209/aaqr.2015.05.0319
|View full text |Cite
|
Sign up to set email alerts
|

Long Term Trends in New York: PM2.5 Mass and Particle Components

Abstract: Measurements of PM 2.5 mass and particle components over a 14-15 year period are used to explore trends at urban and rural locations across New York State. Such data are used to determine compliance with national ambient air quality standards (NAAQS), as well as track the effectiveness of reductions in source pollutant emissions. Since 2000 annual mean PM 2.5 mass shows a downward trend with decreases of 4-7 µg m -3 in urban areas versus 3-4 µg m -3 for rural background sites. Much of this change can be attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…Studies showed that AOD in China had increased until around 2007 and has decreased over the last decade de Leeuw et al, 2018;Sogacheva et al, 2018;Zhang et al, 2017;Zhao et al, 2017). These satellite-based AOD trends are generally consistent with previous studies based on atmospheric visibility (Che et al, 2007;Hu et al, 2017;Li et al, 2016) or ground-based aerosol properties, such as PM 2.5 (Hasheminassab et al, 2014;Kim et al, 2015;Rattigan et al, 2016;Yang et al, 2018). Long-term trends in cloud properties, such as liquid water path (LWP), cloud effective radius (CER), cloud optical thickness (COT), and cloud droplet number concentration (CDNC), have also been examined (e.g., Bennartz & Rausch, 2017;Elsaesser et al, 2017;Li et al, 2018;Manaster et al, 2017;McCoy et al, 2018;Mishra, 2019;Sreekanth, 2016;Stengel et al, 2017;Zhao et al, 2016).…”
Section: Introductionsupporting
confidence: 90%
“…Studies showed that AOD in China had increased until around 2007 and has decreased over the last decade de Leeuw et al, 2018;Sogacheva et al, 2018;Zhang et al, 2017;Zhao et al, 2017). These satellite-based AOD trends are generally consistent with previous studies based on atmospheric visibility (Che et al, 2007;Hu et al, 2017;Li et al, 2016) or ground-based aerosol properties, such as PM 2.5 (Hasheminassab et al, 2014;Kim et al, 2015;Rattigan et al, 2016;Yang et al, 2018). Long-term trends in cloud properties, such as liquid water path (LWP), cloud effective radius (CER), cloud optical thickness (COT), and cloud droplet number concentration (CDNC), have also been examined (e.g., Bennartz & Rausch, 2017;Elsaesser et al, 2017;Li et al, 2018;Manaster et al, 2017;McCoy et al, 2018;Mishra, 2019;Sreekanth, 2016;Stengel et al, 2017;Zhao et al, 2016).…”
Section: Introductionsupporting
confidence: 90%
“…31 Our study takes place in Upstate New York, a region with relatively low air pollution. 32 The PM 2.5 concentrations studied reflected this relatively small range of exposure during the study period. The lack of variability may explain the weak association with prenatal exposures, but the findings also merit attention since we still see evidence of some effect even in an area with low levels of pollution.…”
Section: Discussionmentioning
confidence: 85%
“…Nitric oxides originating from stationary power plants are important pollutants causing a series of serious environmental problems, such as acid rain, ozone depletion, photochemical smog and greenhouse gas (Sahu, 2015;Zahaf, 2015;Lu et al, 2016;Rattigan et al, 2016). Selective catalytic reduction (SCR) has been proved to be an effective technology for the reduction of NO x by NH 3 over different catalysts due to its high efficiency and economic efficiency (Yu, 2015;Jiang et al, 2017;Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%